Another Brooklyn : a novel - Woodson, Jacqueline (Amistad, an imprint of HarperCollins Publishers, 2016)
For August, running into a long-ago friend sets in motion resonant memories and transports her to a time and a place she thought she had mislaid: 1970s Brooklyn, where friendship was everything. August, Sylvia, Angela, and Gigi shared confidences as they ambled their neighborhood streets, a place where the girls believed that they were amazingly beautiful, brilliantly talented, with a future that belonged to them. But beneath the hopeful promise there was another Brooklyn, a dangerous place where grown men reached for innocent girls in dark hallways, where mothers disappeared, where fathers found religion, and where madness was a mere sunset away. Woodson heartbreakingly illuminates the formative period when a child meets adulthood -- when precious innocence meets the all-too-real perils of growing up. --